The Novel Anaerobiosis-Responsive Overlapping Gene ano Is Overlapping Antisense to the Annotated Gene ECs2385 of Escherichia coli O157:H7 Sakai - Hücker, Sarah M.; Vanderhaeghen, Sonja; Abellan-Schneyder, Isabel; Scherer, Siegfried; Neuhaus, Klaus (Frontiers in Microbiology, 2018)
Current notion presumes that only one protein is encoded at a given bacterial genetic locus. However, transcription and translation of an overlapping open reading frame of 186 bp length were discovered by RNAseq and RIBOseq experiments. This open reading frame is almost completely embedded in the annotated L,D-transpeptidase gene ECs2385 of Escherichia coli O157:H7 Sakai in the antisense reading frame -3. The open reading frame is transcribed as part of a bicistronic mRNA, which includes the annotated upstream gene ECs2384, encoding a murein lipoprotein. The transcriptional start site of the operon resides 38 bp upstream of the ECs2384 start codon and is driven by a predicted σ70 promoter, which is constitutively active under different growth conditions. The bicistronic operon contains a ρ-independent terminator just upstream of the novel gene, significantly decreasing its transcription. The novel gene can be stably expressed as an EGFP-fusion protein and a translationally arrested mutant of ano, unable to produce the protein, shows a growth advantage in competitive growth experiments compared to the wild type under anaerobiosis. Therefore, the novel antisense overlapping gene is named ano (anaerobiosis responsive overlapping gene). A phylostratigraphic analysis indicates that ano originated very recently de novo by overprinting after the Escherichia/Shigella clade separated from other enterobacteria. Therefore, ano is one of the very rare cases of overlapping genes known in the genus Escherichia.